2005
DOI: 10.1182/blood-2004-12-4709
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-γ agonists inhibit toll-like receptor-mediated activation of dendritic cells via the MAP kinase and NF-κB pathways

Abstract: Dendritic cells (DCs) play an important role in initiating and maintaining primary immune responses. However, mechanisms involved in the resolution of these responses are elusive. We analyzed the effects of 15d-PGJ2 and the synthetic peroxisome proliferator-activated receptor (PPAR)-gamma ligand troglitazone (TGZ) on the immunogenicity of human monocyte-derived DCs upon stimulation with toll-like receptor (TLR) ligands. Activation of PPAR-gamma resulted in a reduced stimulation of DCs via the TLR ligands 2, 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
141
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(152 citation statements)
references
References 63 publications
(57 reference statements)
10
141
0
1
Order By: Relevance
“…Additionally, we show that PPAR␥ activation decreased LPSinduced phosphorylation of ERK1, thus interfering with MAPK signaling. This is in line with observations made by Appel et al (35), who showed that the PPAR␥ agonist troglitazone interfered with TLR ligand-induced MAPK signaling in human DCs resulting in reduced DC activation. Thus, it appears that the immunostimulatory capacity of DCs is stringently controlled by regulatory mechanisms that involve signaling via PPAR␥.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, we show that PPAR␥ activation decreased LPSinduced phosphorylation of ERK1, thus interfering with MAPK signaling. This is in line with observations made by Appel et al (35), who showed that the PPAR␥ agonist troglitazone interfered with TLR ligand-induced MAPK signaling in human DCs resulting in reduced DC activation. Thus, it appears that the immunostimulatory capacity of DCs is stringently controlled by regulatory mechanisms that involve signaling via PPAR␥.…”
Section: Discussionsupporting
confidence: 93%
“…PPAR-␥ is expressed in both murine CD4 and CD8 cells, and PPAR-␥ ligands directly decrease IFN-␥ expression in T cells (20). In dendritic cells, PPAR-␥ agonists have been shown to inhibit TLR-mediated activation of dendritic cell via the MAP kinase and NF-B pathways (21). However, the effect of PPAR-␥ on IFN-␤ production downstream of TLR signaling has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, zymosan as a ligand for dectin-1 was used together with LPS to stimulate DCs in this model. In contrast, LPS alone was sufficient to stimulate p38 MAPK phosphorylation on Thr 180 and Tyr 182 (21). Before TLR stimulation, interestingly, day 3 ROS lo DCs showed a higher level of background NF-kB p65 phosphorylation and a lower level of p38 MAPK activation than did day 6 ROS hi DCs, suggesting the constitutive presence of a diverse FIGURE 1.…”
Section: Day 6 Rosmentioning
confidence: 96%